PENERIMAAN PLATFORM QUIZIZZ DALAM PEMBELAJARAN INFORMATIKA: INTEGRASI TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN INTRINSIC MOTIVATION INVENTORY (IMI) PADA SMPN 3 SUSUKAN BANJARNEGARA - Titi Safitri Maharani; Rujianto Eko Saputro (Jurnal Riset Teknik Komputer, 2026)
The use of technology in education has rapidly developed, particularly in assessment methods. This study aims to analyze the acceptance of Quizizz in learning by applying the Technology Acceptance Model (TAM) and the Intrinsic Motivation Inventory (IMI) approaches. Data were collected from 222 respondents at SMPN 3 Susukan who actively used Quizizz and were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The analysis results show that in the TAM model, Attitude Toward Using (AM) had the strongest influence on Behavioral Intention (BI) (β = 0.744; p < 0.001), while Self-Efficacy (SE) and Technology Facilitating Conditions (TF) significantly influenced Perceived Ease of Use (PEU). However, Perceived Usefulness (PU) and PEU did not have a significant effect on BI. Meanwhile, the IMI model showed that intrinsic motivation has not formed a strong structural pattern in explaining technology acceptance. The study concludes that cognitive-perceptual factors are more dominant than affective-motivational factors in influencing acceptance.